A first-principles study of the thermoelectric properties of rhombohedral GeSe. Issue 4 (8th January 2020) - Yuan, Kunpeng; Sun, Zhehao; Zhang, Xiaoliang; Gong, Xiaojing; Tang, Dawei
Abstract : This work offers insights into the thermoelectric transport properties in rhombohedral GeSe by first-principles calculations and demonstrates that both p-type and n-type GeSe are potential high-performance thermoelectric materials. Abstract : Manipulation of crystal symmetry is an important strategy to tune the thermoelectric performance. High-symmetry thermoelectric materials benefit from high band degeneracy. With first-principles calculations and Boltzmann transport theory, we systematically investigate the electronic and phononic transport properties of rhombohedral GeSe with higher symmetry. At optimized carrier concentrations, the maximum power factors are found to be 5.86 mW m −1 K −2 for the p-type and 4.45 mW m −1 K −2 for the n-type, respectively. The high p-type power factor originates from the highly degenerated L and Σ bands and small energy offset between them, while the n-type one results from the weak electron–phonon coupling. More importantly, rhombohedral GeSe possesses anisotropic and low lattice thermal conductivities of 3.58 W m −1 K −1 and 1.96 W m −1 K −1 at room temperature in the intralayer and interlayer directions, respectively, which is associated with the giant phonon anharmonicity driven by the resonant bonding. Combining the high power factor and low thermal conductivity, the predicted ZT values for p-type and n-type doping can reach 2.02 and 2.37 at 800 K. This study offers insights into the thermal and charge transport properties in rhombohedral GeSe, and demonstrates that both p-type and n-type GeSe are potential high-performance thermoelectric materials.